2015
DOI: 10.1186/s40842-015-0015-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of nurse satisfaction using insulin pen devices with safety needles: an exploratory factor analysis

Abstract: BackgroundA paucity of data exists to examine nurses’ satisfaction with the use of insulin pens with safety needles in hospitalized patients with diabetes. We investigated major determinants of nurses’ preference of the method of insulin administration in the context of a General Hospital in Northern Italy.MethodsConsecutive patients admitted to three hospital units of different care intensity requiring insulin received insulin therapy through either the vial/syringe method (October to December 2012) or pen/sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Insulin pens are the subject of an FDA warning because of potential blood-borne diseases, and care should be taken to follow the label insert "For single patient use only" (33). Recent reports, however, have indicated that the inpatient use of insulin pens appears to be safe and may be associated with improved nurse satisfaction compared with the use of insulin vials and syringes (34)(35)(36).…”
Section: Continuous Glucose Monitoringmentioning
confidence: 99%
“…Insulin pens are the subject of an FDA warning because of potential blood-borne diseases, and care should be taken to follow the label insert "For single patient use only" (33). Recent reports, however, have indicated that the inpatient use of insulin pens appears to be safe and may be associated with improved nurse satisfaction compared with the use of insulin vials and syringes (34)(35)(36).…”
Section: Continuous Glucose Monitoringmentioning
confidence: 99%
“…Published data report that insulin injection pen-related injury is the most common injury, accounting for 26% of all sharp injuries (Zhao et al, 2019). The introduction of SPN, with an incorporated SIPF, is an advantage over the traditional pen needles reducing the risk of injury and the spread of infectious diseases (Bossi et al, 2016; Floch, 2014; Veronesi et al, 2015). The DropSafe SPN was designed for use with pen injectors and has an automatic needle lockout after use as well as the ability to visually confirm the fluid flow through the needle and that the needle is in the lockout position and a protective sliding shield.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin pens are the subject of an FDA warning because of potential blood-borne diseases, and care should be taken to follow the label insert "For single patient use only." Recent reports, however, have indicated that the inpatient use of insulin pens appears to be safe and may be associated with improved nurse satisfaction compared with the use of insulin vials and syringes (27)(28)(29).…”
Section: Antihyperglycemic Agents In Hospitalized Patientsmentioning
confidence: 99%